The roles of macrophages and monocytes in COVID-19 Severe Respiratory Syndrome - Jun Li; Rui Shan; Heather Miller; Alexander Filatov; Maria G. Byazrova; Lu Yang; Chaohong Liu (Cell Insight, 2025)
The global COVID-19 pandemic has highlighted the pivotal role of the immune system in the development of severe respiratory symptoms, termed COVID-19 Severe Respiratory Syndrome (COVID-19-SR). This review aims to dissect the involvement of lung macrophages and monocytes in orchestrating immune responses to SARS-CoV-2, influencing disease severity and outcomes. Initially, we provide an overview of SARS-CoV-2's invasion process and the body's primary immune defense mechanisms, including the antibody complement system and cytokine production. We then delve into the roles of the monocyte-macrophage system in mediating hyperinflammation and cytokine storms, discussing how abnormal cytokine and chemokine levels contribute to disease progression. Subsequent sections examine the perturbations and overactivation of the monocyte-macrophage compartment during infection, linking these changes to the observed immune dysregulation in COVID-19 patients. In light of these insights, we explore therapeutic strategies targeting macrophages, such as dexamethasone, antisense lipid nanoparticles(ALN), and inhaled recombinant human granulocyte-macrophage colony-stimulating factor (rh-GM-CSF), which aim to modulate inflammation, suppress viral replication, and enhance viral clearance. Additional potential treatments include GSDMD inhibitors and GPR183 antagonists, which warrant further investigation. This review synthesizes current understanding of the immunopathology underlying COVID-19-SR, proposing macrophage- and monocyte-centered therapeutic avenues and outlining future research priorities essential for advancing clinical management and improving patient outcomes.